Phosphorus Fertilizer Rate for Fresh Market Potato Cultivars Grown in Tropical Soil with Low Phosphorus Availability - Fernandes, Adalton M. [UNESP]; Soratto, Rogério P. [UNESP] (Springer Nature, 2016)
Knowledge on phosphorus (P) response of main potato cultivars is essential to rational fertilization management and maximize yield, mainly in tropical soils that usually have low P availability. An experiment was conducted to evaluate the effect of P fertilization rates (0, 125, 250, 500, and 1000 kg P2O5 ha−1) on leaf nutrient concentrations, tuber yield and size distribution, as well as applied P-use efficiency (APUE) in the potato cultivars Agata and Mondial. The results indicated that it is not necessary to evaluate the P-nutritional status and adjust P recommendations on a cultivar basis because P fertilization resulted in similar increases in the leaf P concentration of both cultivars, and the cultivars responded to the same P rate (500 kg P2O5 ha−1). However, Mondial had a higher APUE and was more responsive than Agata to the same P rate. A leaf P concentration of 2.9 g kg−1 was superior to 2.5 g kg−1 as the lower limit of the P sufficiency range for Agata and Mondial.
Keywords: Applied P-use efficiency; Foliar diagnosis; Solanum tuberosum; Tuber number; Tuber size; Tuber yield